Internalization of Ngaben ceremony values in history learning to enhance students' cultural literacy and social attitudes - Mudana, I Wayan; Widiana, I Wayan; Kurniawan, Made Ferry (LPMPP Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the impact of internalizing the values of the Ngaben ceremony in history learning on students' cultural literacy and social attitudes. The research employs a quantitative approach using a quasi-experimental design. The study adopts a posttest-only control group design and was conducted in senior high schools in Buleleng Regency, Bali Province, with a total population of 547 students. The sample was selected using a random sampling technique, resulting in 61 students divided into experimental and control groups. Data collection was carried out using a questionnaire method. Cultural literacy was measured using a cultural literacy questionnaire, while social attitudes were assessed through a social attitude questionnaire. The data were analyzed quantitatively using descriptive and inferential statistical methods. Hypothesis testing was conducted using Multivariate Analysis of Variance (MANOVA). The results indicate that the F-values for Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root were 12.710, with a significance value of 0.000 (lower than the significance threshold of 0.05). These findings suggest a significant simultaneous difference in cultural literacy and social attitudes between students who received history instruction incorporating the values of the Ngaben ceremony and those who did not. Various components supporting the Ngaben ceremony demonstrate its strong association with cultural activities, enhancing students' cultural literacy. The essence of the Ngaben ceremony lies in its educational values, which can be instilled in students to shape their social attitudes.